Does Pre-Service Elementary Teachers’ Attitude Towards Science Affect Their Science Teaching Efficacy? - Nur Afifah; Supartinah; Pratiwi Pujiastuti (Postgraduate, University of Mataram, 2023)
The Primary School Teacher Education Study Programme is responsible for preparing community members who have academic qualifications and competencies as learning agents. This readiness is the main capital for students to do the work of a teacher. In providing education to students, a teacher should have self-efficacy. This research is a quantitative study with an ex-post facto research type. The objectives of this study determine whether there is an effect of attitudes toward science on the efficacy of teaching science subjects. 147 4th-semester students majoring in Elementary School Teacher Education, Yogyakarta State University, were involved. The data collection technique used a questionnaire using a Dimensions of Attitude Towards Science (DAS) Instrument and The Science Teaching Efficacy Belief Instrument (STEBI-B). The study revealed a significant influence between attitudes toward science and the science teaching efficacy of elementary school teacher education students. The results of the analysis revealed that the coefficient of determination is 0.322, which means that 32.2% of variations in science teaching efficacy can be explained by attitude towards science. Â